2022
DOI: 10.3389/fpain.2022.956117
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of pain and disability on the transition from acute to chronic pain-related TMD: A 3-month prospective cohort study

Abstract: Although most cases of pain-related temporomandibular disorders (TMD) are mild and self-limiting, about 10% of TMD patients develop severe disorders associated with chronic pain and disability. It has been suggested that pain intensity contributes to the transition from acute to chronic pain-related TMD. Therefore, the aims of this current prospective cohort study were to assess if pain intensity, pain always being present, pain or stiffness on awakening, jaw activities, and interference, were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Approximately 31% of adults or elderly people suffer from TMD [ 1 ]. Since the late 20th century, several researches have shown that TMD patients usually experience pain, disability and diminished quality of life [ 2 ]. Specifically, self-reported jaw masticatory function declines and general somatic symptoms and pressure pain sensitivity in the orofacial region increase.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 31% of adults or elderly people suffer from TMD [ 1 ]. Since the late 20th century, several researches have shown that TMD patients usually experience pain, disability and diminished quality of life [ 2 ]. Specifically, self-reported jaw masticatory function declines and general somatic symptoms and pressure pain sensitivity in the orofacial region increase.…”
Section: Introductionmentioning
confidence: 99%
“…It is a common health condition worldwide with an estimated prevalence ranging from 11% to 31%, and is especially high in people with multiple sclerosis [ 3 , 4 ]. After a new episode of TMD, 27% of people persist with significant pain one year later [ 5 , 6 , 7 ], and recurrence is common [ 8 ]. Its related pain and disability bring direct (e.g., use of medication to alleviate symptoms) and indirect (e.g., productivity loss) costs [ 9 , 10 , 11 , 12 , 13 ]; therefore, effective management of the condition is important.…”
Section: Introductionmentioning
confidence: 99%